Low temperature solder alloys for ultrasonic soldering of glass - Mustafa, Yusri; Hilmy, Irfan; Adesta, Erry Yulian Triblas (Asian Research Publishing Network (ARPN), 2015)
The research focused on improving the adhesion of low melting temperature lead free solders to soda lime glass through ultrasonic soldering. All soldering parameters involving temperature, time, vibration amplitude and frequency were kept constant except for the new alloying elements to Sn40Bi solders. Improvement on adhesion strength of Sn40Bi solders was attempted by alloying with Al, Mg, Zn and Ag elements. Tensile test was applied on soldered specimen to determine shear separation strength. The positive effect of metal oxide passivation from alloying elements was observed on the adhesion strength. Tensile test and thermogravimetry analysis were applied to determine mechanical and chemical properties of selected solder alloys (Sn40Bi) 0.3 Mg and (Sn40Bi) 0.5Al. Scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDX) were used to examine the bonding mechanism of the selected solders to glass. Sn and Bi were observed to remain in metallic form without adhering to glass. Mg and Al were observed to passivate to metal oxide form. MgO from (Sn40Bi) 0.3 Mg forms metal oxide bond to glass. Al2O3 from (Sn40Bi) 0.5Al forms metal oxide bond to glass.